Validation of the Hepatocyte-like HPCT-1E3 Cell Line as an In Vitro Model for the Prediction of Acute In Vivo Toxicity. Issue 5 (November 2013) - Halwachs, Sandra; Lakoma, Cathleen; Honscha, Walther
In a pilot study, we tested 20 randomly-selected chemicals for their cytotoxicity toward the HPCT-1E3 cell model, in order to prove the ability of this in vitro model to predict human acute in vivo toxicity. The study revealed that, in contrast to most other in vitro models, results from the HPCT-1E3 cell-based system show better correlation with the more-relevant human acute lethal doses, whereas results from most other systems have a high predictivity for human lethal serum concentrations. For the prevalidation of the HPCT-1E3 model as a surrogate for regulatory acute in vivo toxicity tests, we have now expanded the list of tested chemicals to 57 substances, and have compared the results with data from the HepG2 cell assay. Again, a better correlation of HPCT-1E3 IC50 values with human oral lethal doses, as compared to correlation with human lethal serum concentrations, was observed after the pooling of all the tested substances ( r 2 = 0.53 [ P < 0.001] and r 2 = 0.41 [ P = 0.009], respectively). Therefore, the HPCT-1E3 in vitro model may be a valuable tool for prediction of human oral toxicity, and may help to further reduce the number of animals used for in vivo toxicity tests.